Immanent philosophy of X. (February 2016) - Hendry, Robin Findlay
Abstract: In this paper I examine the relationship between historians, philosophers and sociologists of science, and indeed scientists themselves. I argue that (i) they co-habit a shared intellectual territory (science and its past); and (ii) they should be able to do so peacefully, and with mutual respect, even if they disagree radically about how to describe the methods and results of science. I then go on to explore some of the challenges to mutually respectful cohabitation between history, philosophy and sociology of science. I conclude by identifying a familiar kind of project in the philosophy of science which seeks to explore the worldview of a particular scientific discipline, and argue that it too has a right to explore the shared territory even though some historians and sociologists may find it methodologically suspect. Highlights: In this paper I examine the relationship between historians, philosophers and sociologists of science, and indeed scientists themselves. I argue that they co-habit a shared intellectual territory science and its past and should be able to do so peacefully, and with mutual respect. I then go on to explore some of the challenges to mutually respectful cohabitation between history, philosophy and sociology of science.